2021
DOI: 10.3390/ijerph182111648
|View full text |Cite
|
Sign up to set email alerts
|

Association between Exposure to Particulate Matter during Pregnancy and Multidimensional Development in School-Age Children: A Cross-Sectional Study in Italy

Abstract: Air pollutants can potentially affect the development of children. However, data on the effect of exposure to air pollution during pregnancy and developmental outcomes in school children are rare. We investigated the link between prenatal exposure to particulate matters smaller than 10 microns (PM10) and the development of school-age children in multiple domains. Cross-sectional data were collected in Italy between 2013 and 2014. Children aged between 5 and 8 years (n = 1187) were assessed on cognitive, commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…These findings are in line with a few recent studies on early life air pollution exposure and cognitive domains in children. Specifically, associations have been found in recent studies for second trimester air pollution exposure and cognitive and communicative scores in children [ 18 ]. Additionally, other studies have found impacts from prenatal air pollution exposure and deficits in fine motor skills [ 17 ] and general facets of behavioral development [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in line with a few recent studies on early life air pollution exposure and cognitive domains in children. Specifically, associations have been found in recent studies for second trimester air pollution exposure and cognitive and communicative scores in children [ 18 ]. Additionally, other studies have found impacts from prenatal air pollution exposure and deficits in fine motor skills [ 17 ] and general facets of behavioral development [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studying the impacts of environmental exposures on continuous cognitive and adaptive symptoms in children allows for the assessment of subclinical impacts and uses a more dimensional approach [ 16 ]. A few recent studies have found associations between prenatal and early postnatal air pollution exposure and several continuous cognitive outcomes in children in the general population, particularly for communicative domains, motor skills, and overall cognitive deficits [ 17 , 18 , 19 ]. Several additional questions remain including the specific window of susceptibility and whether associations are similar for children with and without ASD or a developmental delay (DD).…”
Section: Introductionmentioning
confidence: 99%